Participatory pattern workshops: a methodology for open learning design inquiry - Niall Winters; Steven Warburton; Yishay Mor (Association for Learning Technology, 2012)
In order to promote pedagogically informed use of technology, educators need to develop an active, inquisitive, design-oriented mindset. Design Patterns have been demonstrated as powerful mediators of theory-praxis conversations yet widespread adoption by the practitioner community remains a challenge. Over several years, the authors and their colleagues have facilitated many workshops in which participants shared experiences, captured these as design narratives, extracting design patterns, and applied them to novel teaching challenges represented as design scenarios. This paper presents the core elements of the methodology that emerged from these workshops: the Participatory Patterns Workshops (PPW) methodology.